A COMPARATIVE ANALYSIS BETWEEN THE CUSTOMARY AND ISLAMIC LAWS OF INTESTATE SUCCESSION WITH REGARD TO DISCRIMINATION: A SOUTH AFRICAN CONSTITUTIONAL LAW CASE STUDY - Abduroaf, Muneer (Jurnal Syariah, 2023)
The law rule of male primogeniture (customary law of succession) was found to be unconstitutional in Bhe and Others v The Magistrate Khayelitsha and Others (Bhe) based on it unfairly discriminating against females. The Constitutional Court held that the rule of male primogeniture was inconsistent with the Constitution and invalid to the extent that it ‘excludes or hinders women … from inheriting property.’ Muslims have been living in South Africa for over 300 years. These persons are required in terms of their religion to follow Islamic law. There has (to date) been no legislation enacted by the South African government that gives effect to the Islamic law of succession. A Muslim daughter could argue that the Islamic law of intestate succession per se discriminates against females, as a Muslim son would always inherit double the share of a Muslim daughter. This article compares the position of females in terms of the customary and Islamic laws of intestate succession. An overview of the South African law of intestate succession is provided by way of introduction. This is followed by examining certain South African intestate succession law court cases where discriminatory provisions were challenged. The 2:1 rule as found within the Islamic law of intestate succession per se is then investigated. The article then examines the constitutionality of the 2:1 rule as found within the Islamic law of intestate succession per se based on the same constitutional principles applied in the Bhe judgment where the constitutionality of the rule of male primogeniture was investigated. The article concludes with an analysis of the findings and a recommendation.